Typification of five names listed by Roberto de Visiani in Plantarum Serbicarum Pemptas - Clementi, Moreno; Kuzmanović, Nevena; Barina, Zoltan; Lakušić, Dmitar; Vukojičić, Snežana (Phytotaxa, 2014)
Roberto de Visiani (1800–1878) was a Dalmatian botanist of Italian ancestry. During the 1850s he started a long lasting collaboration with a Serbian professor - botanist Josif Pančić (1814–1888), who worked in Belgrade. During this period, from 1858 to 1871, they described thirty-five new species and one new variety, in four articles (Visiani 1860, Visiani & Pančić 1862, Visiani & Pančić 1865, Visiani & Pančić 1870). Many of their names are still in general use or are basionyms of the names in use (Euro+Med 2014), but, with few exceptions, they have not yet been typified.